Examining the Functioning of Organizations from the Aspects of Organizational Culture and Leadership - Awasthi, Ridhi; Ali, Syed Mansub (International Journal of Engineering and Management Sciences, 2018)
Organizational culture and Leadership both have been under research for a long time, as they play a vital role in the performance of an organization. The organizational culture is the set of rules or acts as a guidebook of an organization for achieving the objectives while leadership defines these rules and implements them as well. Organizational culture is dependent to a great extent on the norms and values of the society or the country where it is located. Important for achieving the objectives of an organization, this factor plays a vital role while setting the organizational culture. Incorporating organizational culture and then sustaining it is done by the leaders. Leadership if does not play an effective role in regards to implementation of the organizational culture, can collapse the organizational structure. Leaders are required to develop the qualities according to the organizational culture and should be responsible to come forward to transform if necessary and implement the system. The organizational culture should fulfill the needs of the organization’s goals and the norms of the society. Both leadership and organizational culture are co-dependent on each other and should be understood together.